Play Therapy for Children's Behavioural Issues: Pre-post Intervention Analysis - Rekha K S, (Disease and Health: Research Developments Vol. 1, 2024)
This chapter examines the effectiveness of play therapy in reducing behavioral problems among children aged 3 to 7 years enrolled in pre-primary education at an unaided school. Behavioral issues were identified through assessments by qualified educational counselors. A total of 42 students participated in structured play therapy sessions. To evaluate the therapy's impact, a pre-test and post-test design was employed, with assessments conducted before and after the intervention. The findings reveal a significant reduction in behavioral problems following play therapy, highlighting its potential as an effective intervention for early childhood behavioral issues.